Tourism Industry Perspectives in the Context of the COVID-19 Pandemic Based on the Sustainable Development Concept - Almukhamedova, Olga (International Journal of Criminology and Sociology, 2022)
The relevance of this study is in the growing popularity of the concept of sustainable development in the tourism sector. The purpose of the article is to determine a systematic basis for the assessment of the possibility of sustainable tourism development at the regional level, as well as determining relevant vectors. In addition, the study considers a number of studies that allow for defining sustainable tourism, as well as determining groups of indicators affecting it. The leading method of studying tourism structure as part of a regional socio-economic system is topological analysis, which allows for identifying functionally significant combinations of factors. Incidence matrices of the structure of indicators with included weighting factors influencing the sustainable development of tourism, analysis of their q-connectivity, the results of the dimension of simplexes, the number of connected components and communication chains, the structural vectors of the complexes were determined and presented. The study proved the presence of simplexes in the complexes. The effects on simplexes can bring the desired result in the quickest and most efficient way. Since tourism is an integral part of environmental, social and economic sectors, and the sustainable development itself can be regarded as a unified system of interaction between them, it is possible to use the above factors in each of the sectors on a case-by-case basis in any territory or enterprise to conserve resources, eradicate poverty and ensure well-being. This research attempts to formalize the factors that determine the sustainable development of tourist destination that gives the full basis for a systematic study of the territory to assess the sustainability of tourism development. The topological analysis shows the mutual influence of simplicial complexes by means of a chain of connections leading to sustainable development.